Effect of energy transfer and local crystal field perturbation on the thermometric sensitivity of Ga-Tb-Eu ternary emission system. Issue 1 (1st January 2022) - Yang, Xuening; Li, Xiao; Li, Yongcheng; Shang, Jiaxiang; Ma, Bin
Abstract: A series of optical thermometers based on Eu 3+ /Tb 3+ doped Y3 Ga5 O12 with self-excited GaO6 group phosphors were designed through controllable energy transfer and local crystal field perturbation simulated using the density-functional theory approach and related structures. Color-tunable properties of the phosphors could be achieved through controllable energy transfer. In addition, the thermometers exhibited superb temperature sensitive properties. Over the entire temperature range (298.15–598.15 K), maximum values of the absolute sensitivity and relative sensitivity are 0.028 K −1 and 7.03 %K −1, respectively. Meanwhile, the thermometer has outstanding resolution (ΔT = 0.0043 K) and repeatability (98.37%).